2017
DOI: 10.2147/ott.s125579
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginyl endopeptidase improves the resistance of microtubule-targeting drugs in gastric cancer through IQGAP1 modulating the EGFR/JNK/ERK signaling pathway

Abstract: PurposeIn recent years, understanding of the role of asparaginyl endopeptidase (AEP) in tumorigenesis has steadily increased. In this study, we investigated whether AEP expression correlates with sensitivity to chemotherapeutic drugs in gastric cancer and explored the mechanism.Patients and methodsAEP expression in the serum of patients’ peripheral blood was measured by enzyme-linked immunosorbent assay. Patient survival time was evaluated using univariate and multivariate analyses. Mass spectrometry and co-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…2 ). We found that plenty of cytoskeleton related proteins identified in our data, such as Vimentin, Cortactin, and IQ Motif Containing GTPase Activating Protein 1 (IQGAP1), also have been revealed in gastric cancer [ 43 ]. More, endogenic coimmunoprecipitation (co-IP) assays revealed that AEP interacted with Tmod3 in GBM cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). We found that plenty of cytoskeleton related proteins identified in our data, such as Vimentin, Cortactin, and IQ Motif Containing GTPase Activating Protein 1 (IQGAP1), also have been revealed in gastric cancer [ 43 ]. More, endogenic coimmunoprecipitation (co-IP) assays revealed that AEP interacted with Tmod3 in GBM cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting IQGAP1 re-sensitized these cells to trastuzumab treatment in vitro, indicating a role of IQGAP1 in mediating trastuzumab resistance [155]. In patients treated with taxane-containing chemotherapy, levels of asparaginyl endopeptidase (AEP) increase and play an important role in acquired drug resistance [156]. AEP interacts with IQGAP1 and possibly contributes to drug resistance through IQGAP1-mediated RAS-MAPK signaling [156].…”
Section: Iqgap1 In Gastric Cancermentioning
confidence: 99%
“…In patients treated with taxane-containing chemotherapy, levels of asparaginyl endopeptidase (AEP) increase and play an important role in acquired drug resistance [156]. AEP interacts with IQGAP1 and possibly contributes to drug resistance through IQGAP1-mediated RAS-MAPK signaling [156].…”
Section: Iqgap1 In Gastric Cancermentioning
confidence: 99%
“…Gene Ontology Biological process (GO-BP) analysis showed that the differentially expressed genes were primarily involved in negative regulation of endopeptidase activity, cell adhesion, inflammatory response, and O-glycan processing (Figures 2C,D). These biological functions are closely related to the development and prognosis of GC (Duarte et al, 2016;Cui et al, 2017;Mukai et al, 2017;Geng et al, 2018).…”
Section: Differential Gene Expression and Hub Genesmentioning
confidence: 99%